Endocrine and Cognitive Adaptations to Cope with Stress in Immature Common Marmosets (Callithrix jacchus): Sex and Age Matter - Sousa, Maria Bernardete Cordeiro de; Galvão, Ana Cecília de Menezes; Sales, Carla Jéssica Rodrigues; Castro, Dijenaide Chaves de; Galvão-Coelho, Nicole Leite (Frontiers in Psychiatry, 2015)
Phenotypic sex differences in primates are associated with body differentiation during the early stages of life, expressed in both physiological and behavioral features. Hormones seem to play a pivotal role in creating a range of responses to meet environmental and social demands, resulting in better reactions to cope with challenges to survival and reproduction. Steroid hormones actively participate in neuroplasticity and steroids from both gonads and neurons seem to be involved in behavioral modulation in primates. Indirect evidence suggests the participation of sexual steroids in dimorphism of the stress response in common marmosets. This species is an important experimental model in psychiatry, and we found a dual profile for cortisol in the transition from juvenile to subadult, with females showing higher levels. Immature males and females at 6 and 9 months of age moved alone from the family group to a new cage, over a 21-day period, expressed distinct patterns of cortisol variation with respect to range and duration of response. Additional evidence showed that at 12 months of age, males and females buffered the hypothalamic–pituitary–adrenal axis during chronic stress. Moreover, chronic stressed juvenile marmoset males showed better cognitive performance in working memory tests and motivation when compared to those submitted to short-term stress living in family groups. Thus, as cortisol profile seems to be sexually dimorphic before adulthood, age and sex are critical variables to consider in approaches that require immature marmosets in their experimental protocols. Moreover, available cognitive tests should be scrutinized to allow better investigation of cognitive traits in this species.